Simulation of Rainfall Runoff and Pollution Control by Sponge City Based on SWMM— A Case Study of Sponge Demonstration Area in Guangming District, Shenzhen - LU Qiaohui; HUANG Yilong; PENG Zhiren (Renmin Zhujiang)
In order to quantitatively study the control effects of sponge city construction on runoff volume and runoff pollution,taking the sponge demonstration area in Guangming District,Shenzhen as the example,this paper simulates and analyzes the rainfall runoff process under the normal year and rainfall events of different return periods based on SWMM model.The conclusions are as follows:① Sponge city construction could significantly benefit the reduction of runoff volume and runoff pollution,but the effects would decrease if lacking the follow-up maintenance for sponge facilities.② Sponge facilities could evidently reduce the runoff volume and runoff pollution with rainfall return periods less than 5 years.Otherwise,the effects on runoff volume reduction,runoff peak delay,peak runoff volume reduction and suspended solid (SS) removal would weaken.③With the increase of the rainfall intensity,the final SS concentration would decrease under the dual action of sponge and rainfall runoff.The results show that degraded sponge facilities could restrain the control effects on rainfall runoff,which are of significance for sponge city construction and maintenance.